Connective tissue dysplasia as a risk factor for adnexal torsion in adolescent girls - Kiebashvili, Salome; Tuchkina, Iryna (The Ukrainian Scientific Medical Youth Journal, 2022)
the state of somatic and reproductive health of adolescent girls is an actual problem both throughout the world and in Ukraine. Connective tissue dysplasia, a group of congenital pathologies of connective tissue with insufficient or abnormal development of collagen structures, which leads to disruption of the structure and functional disorders of various organs and tissues, was found to be widespread among patients of the pubertal period. More often there are undifferentiated forms of connective tissue dysplasia, characterized by clinical polymorphism: pathology of the musculoskeletal system, autonomic dysfunction syndrome, gynecological pathology, among which adnexal torsion attracts special attention, and more. The aim of the study was to explore the manifestations of connective tissue dysplasia and neurological disorders as risk factors for adnexal torsion, with the aim of improving the clinical and diagnostic approaches to the management of adolescent girls with this gynecological pathology. Based on informed consent, inclusion and exclusion criteria, 42 adolescent girls aged 14-17 years old with a history of adnexal torsion (the clinical group) and 30 healthy peers (the control group) took part in the study. To achieve the set goals, anthropometric, general clinical, echographic and radiological methods, the study of the neurological status were used. In the course of the study, it was found that signs of connective tissue dysplasia were found in 16 (38.1%) of the examined adolescents of the clinical group and in 3 (10%) of the control groups (p<0.05). In particular, scoliosis of the I-II degree was diagnosed in 14 (33.3%) adolescents of the clinical group, which was more than 3 times higher than the similar indicator in the control group - 3 (10%) (p<0.05). In addition, dolichostenomelia and arachnodactyly were observed in adolescents with connective tissue dysplasia, on average, 1.5 times more often. Flat feet was diagnosed 3 times more often in the clinical group (in 13 patients (30.9%)) compared to the control group (in 3 patients (10%)) (p<0.05). At the same time, some patients had a combination of several pathologies disorders of the musculoskeletal system. Thus, scoliosis and flat feet were simultaneously diagnosed in 9 (21.4%) adolescents of the clinical group and only in 2 (6.6%) adolescents in the control group (p<0.05). External developmental anomalies in connective tissue dysplasia were quite often combined with developmental anomalies of internal organs: gallbladder kink was found in 5 (11.9%) patients, nephroptosis - in 2 (4.7%) patients, mitral valve prolapse - in 3 (7.1%) patients of the clinical group, which is associated with the same origin and laying of a number of systems in embryogenesis. The surveyed adolescents of the clinical group had complaints of an asthenic nature associated with autonomic imbalance, namely: rapid heartbeat - in 16 (38.1%), headache - in 12 (28.5%), poor tolerance of moderate physical activity - in 7 (16.6%), increased fatigue - in 9 (21.4%) , sweating – in 7 (16.6%) patients. All adolescent girls were prescribed complex treatment, taking into account the type of autonomic regulation, the severity of clinical and functional disorders that characterize autonomic dysfunction. Thus, as a result of the study, a high prevalence of undifferentiated forms of connective tissue dysplasia was established in patients with a history of adnexal torsion and in most cases was accompanied by the development of pathology of the musculoskeletal system, structural and functional disorders of the internal organs, and manifestations of autonomic dysfunction syndrome. Connective tissue dysplasia, as one of the established predictors of adnexal torsion, can act as an important prognostic marker and provide an opportunity to prevent and timely diagnose the abdominal pain syndrome and its complications caused by this gynecological pathology.